Central nervous system tumors - EKER, NURŞAH; TOKUÇ, AYŞE GÜLNUR; TRUE, ÖMER (My University, 2017)
Background/Objectives: Central nervous system (CNS) tumors are the most common solid tumors in childhood. Our instution is the one of the major referral center for pediatric brain tumors in Turkey. We aimed to analyzed children with brain tumors who were diagnosed and treated at our center in this study. Design/Methods: This is a retrospective study of 96 pediatric patients with brain tumors treated in between 2009 to 2017. Sixteen patients were lost to follow-up and 80 patients were included in the analysis. Demographic informations, histologic subtypes, stage at diagnosis, treatment modalities and outcomes were evaluated, retrospectively. Results: Of the 80 patients, 42 (52.5%) were males, 38.5 (47.5%) were females. The mean age was 6.8 ± 4.6 years (ranging from 0.17 years to 15.5 years). The mean duration of follow up was 30 months. Mean survival time was 71.4 months (95% CI: 61.8 - 80.9). The most common localization was the infratentorial area (38.8%). Among all of the patients, gliomas are the most common histologic form (54 %) and 51,3% had grade IV stage for WHO. Five-year overall survival (OS) is 68 %. The most important factor for OS was tumor total resectabity. Total resectable patients OS was 81% vs gross total resection (GTR) was 49.5% vs partial resection was only 28% within 5 years. The children with diffuse infiltrative pontine glioma (DIPG) and atypical teratoid/rhabdoid tumor (AT/RT) had the worst prognosis and these patients died in the first year of their treatment. Conclusions: In developing countries, as the use of molecular studies could not be routinely performed in clinical practice. Brain tumors are relatively common cancers among children.usually the first and the most important step in therapy. Patients with the most complete resection have significantly longer survival despite all of the technological advances.